DOMBA KISAR SEBAGAI PLASMA NUTFAH LOKAL DI MALUKU - Jerry Fred Salamena; Rajab Rajab (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2018)
This research and paper were conducted and represented as a effort to stipulating the Kisar Sheep as a local genetics germ cell resource in Indonesia, and this step was helpfully to their development and observation in Maluku Province especially. Morphology analysis by using canonical discriminant method was used to defining and determine the difference variable between Kisar sheep with the the other local sheep breed whisch spread over in Indonesia. Pursuant to specific characteristic or appearance, phenotific characteristics and also natural excellence which found on Kisar sheep, it is on the right track for this local livestock breed can be specified officially as one of the type of local sheep breed in Indonesia.